All-cellulose nanocomposite films based on bacterial cellulose nanofibrils and nanocrystals - Nascimento, Eligenes S. (2021)
All-cellulose composites are promising materials due to the expectable strong filler-matrix interaction. In the present work, films based on bacterial cellulose were produced, using nanofibrils as matrix and nanocrystals as filler, as well as glycerol as plasticizer. The effect of the nanocrystals content (05 wt.%) on the mechanical properties, barrier properties, water resistance, and others were investigated. The films presented a high crystallinity index (7679 %) and remarkable tensile strength, elastic modulus and resistance to disintegration in water. The addition of nanocrystals leads to an increase of tensile strength (from 36.9 to 46.5 MPa) and elongation at break (from 8.1 to 13.5%), a decrease of water vapor permeability (17 %), and enhanced water resistance. The elastic modulus was not significantly changed by the incorporation, but it was already high (1.22 GPa) for the neat films. Moreover, all compositions demonstrated biocompatibility after incubation with Caco-2 cells, up to 48 h of contact. The films produced, based on the combination of nanofibrils and nanocrystals of bacterial cellulose, demonstrated great potential for food packaging application.